2009
DOI: 10.2135/cropsci2008.10.0599
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Large‐Scale Simple Sequence Repeats in Jute

Abstract: Jute is an important crop of the Indian subcontinent and comprises tossa jute (Corchorus olitorius) and white jute (C. capsularis). The yield and fiber quality of this crop remained stagnant for many years and could not be improved through conventional plant breeding. Also, no effort has been made to develop molecular markers on a scale required for marker‐assisted selection (MAS) to supplement conventional plant breeding. As a first step toward deploying MAS for jute improvement, 2469 simple sequence repeats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 20 publications
2
28
2
Order By: Relevance
“…Genomic DNAs of RIL lines including mapping parents were screened by using a larger set of genome-wide 2496 pairs of SSR markers (Mir et al 2009) for polymorphism detection. Primer synthesis, selection of polymorphic markers and PCR amplifications were performed.…”
Section: Ssr Genotypingmentioning
confidence: 99%
See 3 more Smart Citations
“…Genomic DNAs of RIL lines including mapping parents were screened by using a larger set of genome-wide 2496 pairs of SSR markers (Mir et al 2009) for polymorphism detection. Primer synthesis, selection of polymorphic markers and PCR amplifications were performed.…”
Section: Ssr Genotypingmentioning
confidence: 99%
“…A total of 86 of 376 genomic DNA-derived SSRs and EST-SSRs (40 %) designed by Mir et al 2009 revealed polymorphism between the parental genotypes, of which 66 were selected for screening of the mapping population on the basis of consistency of amplification. A subset of 48 SSR markers generated data of sufficient quality to generate a framework genetic map, and 40 loci (85 %) were assigned to nine…”
Section: Framework Genetic Map Construction and Selection Of Maximum mentioning
confidence: 99%
See 2 more Smart Citations
“…They are unlimited in number and are not affected by environmental factors, growth stage and agronomic practices (Mir et al 2009). In many studies conducted, the diversity of the genotypes at species level is very low for many accessions of Jute mallow and hence it is important to focus on the variation that exists between different species and establish how this variation can be used to improve the crop.…”
Section: Genetic Diversity Based On Biochemical Markersmentioning
confidence: 99%